2015
DOI: 10.4236/health.2015.72030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Length of Hospital Stay Joining Educational Programs for Type 2 Diabetes Mellitus Patients: Can We Control Medical Costs in Japan?

Abstract: Diabetes has become a growing concern in Japan, both medically and financially. The medical cost of diabetes was estimated at 1215 billion yen for fiscal year 2011. We analyzed the length of stay (LOS) in a hospital for type 2 diabetes mellitus patients who participated in educational programs to determine factors affecting LOS. Data on 991 patients obtained from 28 Red Cross hospitals in 2008 were used. For the analysis, we used the Box-Cox transformation model and Hausman test. The results revealed that pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The data included patients' LOS, medical expenditures, age, gender, health-related conditions and medical treatments. For details, see Nawata and Kawabuchi [23]. The original dataset included 27,861 patients, and 22,430 patients (80%) were classified under the DPC code 100070xxxxxx0x (type 2 diabetes patient without diabetic ketoacidosis and secondary diseases).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The data included patients' LOS, medical expenditures, age, gender, health-related conditions and medical treatments. For details, see Nawata and Kawabuchi [23]. The original dataset included 27,861 patients, and 22,430 patients (80%) were classified under the DPC code 100070xxxxxx0x (type 2 diabetes patient without diabetic ketoacidosis and secondary diseases).…”
Section: Datamentioning
confidence: 99%
“…Using the BC MLE and N-estimator, we can conduct the test for the "small σ" assumption (the null hypothesis is that the "small σ" assumption holds) by the Hausman test [33]. For details, see Nawata and Kawabuchi [23] [24].…”
Section: Nawata's Estimator and The Test For The "Small σ" Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose that ij t is the explanatory variable of observation j in group i (for example, LOS of patient j in hospital i in Nawata and Kawabuchi [6]- [11]). I consider the BC model:…”
Section: Bc Model With Heteroscedastic Disturbancesmentioning
confidence: 99%
“…It is sometimes necessary to consider a model combining these two models. Nawata and Kawabuchi [6]- [11] analyzed length of stay (LOS) in Japanese hospitals using the BC model. They found that the variances among hospitals were often very different among hospitals even after the transformation.…”
Section: Introductionmentioning
confidence: 99%